Supramolecular self-assembly of a nitro-incorporating quinoxaline framework: insights into the origin of fluorescence turn-on response towards the benzene group of VOCs. Issue 20 (16th September 2021) - Basak, Megha; Das, Gopal
Abstract : A nitro incorporating quinoxaline based probe displays remarkable selectivity and sensitivity towards mesitylene amidst all VOCs in aqueous medium along with morphological evolution to higher order stone-shaped aggregates. Abstract : Hazardous volatile organic compounds (VOCs) can significantly impact human health and the environment. Hence, the detection of VOCs is of foremost importance. A quinoxaline-based fluorimetric probe (1) unveils a notable "turn-on" fluorescence response towards mesitylene in the presence of other VOCs and common interfering ions in aqueous media. The sensing phenomenon involves specific 1 : 1 stoichiometric binding of the probe with mesitylene with a ∼2.66 ppm detection limit. Furthermore, the probe experiences morphological transformations from a fibril-network to a stone-shaped hetero-structure upon treatment with mesitylene, indicating mesitylene induced self-assembly. The detection induced self-assembly of the probe was further corroborated by dynamic-light-scattering (DLS) and fluorescence microscopy study. Importantly, this proposed approach is applicable to detect mesitylene in natural water sources and in the vapor phase using portable, low-cost filter paper strips.